Analysis of potassium (K+) efflux systems (Kef) as an antibiotic target in pathogenic bacteria - Haslam, C (2019)
Potassium (K+) efflux systems (Kef) are K+/H+ antiporters found in most Gram-negative bacteria. Kef systems play a vital role in the protection of bacteria from toxic electrophiles by regulating cytoplasmic pH and consequently demonstrate potential as an antibiotic target. Kef is inhibited by glutathione (γ-L-Glu-L-Cys-Gly, GSH) and activated by glutathione S conjugates (GSX). The proposed model of Kef activation in both EcKefC, from Escherichia coli (E. coli), and SdKefQCTDH6, a construct of Kef from Shewanella denitrificans (S. denitrificans), is a single amino acid switch at the F441 or F448 capping residue, respectively. The aims of this dissertation were to confirm the proposed mechanism of Kef activation and to investigate novel Kef systems in pathogenic bacteria as an antibiotic target. In work to probe the mechanism of Kef activation, p-trifluoromethyl-L-phenylalanine (ptfmF) was incorporated into SdKefQCTDH6 at position 448 to give SdKefQCTDH6(F448ptfmF). The conformational change of SdKefQCTDH6(F448ptfmF) upon adding inhibitory or activating ligands was analysed using 19F NMR spectroscopy. The data obtained are consistent with the proposed model for Kef activation: activators displace the capping residue, whereas inhibitors, including GSH, do not. This novel 19F NMR based assay is an efficient method to determine whether a compound is a Kef activator or inhibitor, vital in the design of new Kef ligands. To investigate whether the role played by Kef in E. coli is conserved across Gram negative bacteria, Kef systems were identified in two pathogenic bacteria: Yersinia pestis (YpKefB; with ancillary proteins -G and -P) and Burkholderia pseudomallei (BpKef1 and BpKef2). Dipeptides OXFKEF12–14 were synthesised and tested in E. coli expressing YpKefGBP, BpKef1, or 2 using the Kirby Bauer disc diffusion assay (Figures A and B). In E. coli MJF645 (mutant strain lacking GSH) and Frag 1 (GSH containing strain) expressing YpKefGBP, OXFKEF13 and 14 were active only in the MJF645 transformant, as a zone of growth inhibition/death was observed (Figure A). To rationalise these results, the expression level of YpKefBH6 (a His-tagged variant of YpKefB) was determined using western blotting and was found to be similar in both MJF645 and Frag 1. Due to its sequence similarity to YpKefBH6, it can be inferred that the expression level of YpKefB is also comparable in both cell strains, and so the opposing disc assay results must be caused by another factor. GSH may be inhibiting YpKefB, and so the dipeptides may be unable to outcompete it in the ligand binding site. OXFKEF12–14 could also be being degraded by GSH, giving compounds which inhibit YpKefB or are inert. As OXFKEF12–14 may be unstable in the presence of GSH, we wanted to synthesise dipeptides with improved stability with respect to GSH. Novel thioether analogues with aromatic S substituents were synthesised using the thiol-ene reaction: two methyl esters for the disc assay and their carboxylic acid analogues for biophysical assays. Both carboxylic acids were shown to bind to SdKefQCTDH6 using two orthogonal assays. Both methyl esters did not inhibit or kill MJF645 expressing SdKef or YpKefGBP in the disc assay. The inactivity of the compounds may have been caused by several factors, including their poor solubility. The results indicate that aromatic S substituents are tolerated in terms of Kef binding. In conclusion, we have shown that YpKefB is similar to EcKefC, both in terms of protein structure and function. In contrast, BpKef1 and BpKef2 behave differently from EcKefC. In Burkholderia pseudomallei, the endogenous low molecular weight thiol may not be GSH or the role of its Kef systems may be dissimilar from E. coli.